Utilization Review pada Jaminan Kesehatan Nasional: Implementasi, Tantangan dan Komponen Essensial - Ulandari, Luh Putu Sinthya; Indrayathi, Putu Ayu (Jurnal Ekonomi Kesehatan Indonesia, 2025)
Indonesia has implemented the National Health Insurance (JKN) program since 2014; however, various forms of fraud continue to be found. According to regulations, BPJS Kesehatan, as the national social security agency, is required to conduct Utilization Review (UR) as an effort to control costs and improve the quality of healthcare services. The effectiveness of UR remains questionable due to several implementation challenges. This study aims to explore the implementation of UR, identify its challenges, and examine the essential components required for its effective implementation. The study was conducted in August 2023 using a qualitative approach through in-depth interviews. Samples were selected purposively and consisted of five key informants. Data were analyzed using thematic analysis. The results showed that all respondents had good knowledge of the UR concept. BPJS Kesehatan applies a retrospective method. The UR results vary, including trends or patterns of patient visits, the ten most frequent Case Base Groups (CBG), the ten most common procedures, and the ten cases with the highest funding for outpatient and inpatient services. BPJS Kesehatan also formulates recommendations based on the UR results. However, strong commitment from healthcare providers is required to implement improvements. The challenges faced by BPJS Kesehatan include limited time for conducting UR, the large number of healthcare facilities to be assessed, as well as conflicts and misunderstandings with patients. Regarding essential components, three key aspects are needed: human resources, technology, and standardized UR procedures.